Rate, risk factors, and clinical outcomes of SARS-CoV-2 reinfection vs. primary infection in readmitted COVID-19 patients in Iran: a retrospective cohort study - Shahrbaf, Mohammadamin; Alimohamadi, Yousef; Yousefi Arfaei, Reza; Salesi, Mahmood; Izadi, Morteza; Raei, Mehdi (Frontiers in Public Health, 2024)
Background Corona Virus Disease 2019 (COVID-19) has severely impacted global health, resulting in high morbidity and mortality, and overwhelming healthcare systems, particularly in Iran. Understanding reinfection is crucial as it has significant implications for immunity, public health strategies, and vaccine development. This study aims to identify rate and the risk factors associated with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) reinfection and compare the clinical course of initial infection versus reinfection in readmitted COVID-19 patients in Iran. Methods This retrospective cohort study was conducted from January 2020 to the end of 2022 in five hospitals in Iran. The study compared demographic and clinical data, vaccination status, and clinical outcomes between patients with reinfection (defined as a positive PCR test for SARS-CoV-2 at least 90 days after the primary admission) and a control group (patients who had an initial confirmed SARS-CoV-2 infection but were not readmitted with a positive PCR test for SARS-CoV-2 at least 90 days after their primary infection). Risk factors for reinfection were evaluated using a regression model. Propensity score matching (PSM) was used to compare post-clinical and laboratory outcomes between the matched case and control groups. Results Out of 31,245 patients, 153 (0.49%) experienced reinfections. The reinfection rate was significantly higher during B.1.617.2 and B.1.1.529 variant wave (p < 0.001). After multivariable regression analysis, incomplete vaccination status (OR: 1.68, 95% CI: 1.34–2.31, p = 0.021) and lack of booster vaccination (OR: 2.48, 95% CI: 1.96–3.65, p = 0.001) were the risk factors for reinfection. Furthermore, reinfection was associated with atypical COVID-19 symptoms, and shorter ICU and hospital stays (p < 0.001). The B.1.1.529 variant was significantly more common among reinfected patients (p < 0.001). Conclusion SARS-CoV-2 reinfections are more frequently observed during waves of novel variants and are associated with a milder clinical course and shorter hospital stays. Full vaccination and booster doses can effectively reduce the risk of SARS-CoV-2 reinfections.